Simple new technique for macular pucker peel without forceps - Lumi, Xhevat; Petrovski, Beáta Eva; Petrovski, Goran (Frontiers in Medicine, 2022)
Purpose: To describe the effectiveness and evaluate the anatomical and functional results of surgery for macular pucker (MP) peel using a 25-gauge pars plana vitrectomy (PPV) cutter without forceps. Methods: A prospective consecutive case series of 14 eyes of 14 patients who underwent 25-gauge PPV for MP. The surgical procedure was performed using the new peeling technique. The edge of the membrane was engaged at the opening of the cutter by gradually increasing the vacuum. The peeling process was finished by holding stable vacuum or regrasping the membrane in the same manner. Results: The study included 6 female and 8 male patients with the mean age of 72.3 (range 59-84) years. MP peel was achieved in all cases without the need of microforceps. Patients were followed for at least 6 months. Best corrected visual acuity improved from a mean preoperative 0.6 on a logMAR scale to postoperative 0.23 (P<0.001). Mean preoperative Central Retinal Thickness was significantly reduced from 489.7 µm to 377.6 µm postoperatively (P<0.001). There were no intra- or postoperative complications. Conclusion: MP peel with 25-gauge vitrectomy probe is an alternative simple and safe technique. The technique does not require extra instrumentation. It results in anatomic and functional improvement in all cases.